Paleobotanical Investigations at Sermermiut, Jakobshavn, West Greenland. - Fredskild, Bent (Meddelelser om Grønland, 1967)
Palaeobotanical investigations were undertaken in two transects in a bog at Sermermiut (69°12’ N, 51 °08’ W) near Jakobshavn. Pollen diagrams from three profiles were worked out, and a series of macrofossil samples examined. A series of samples from one of the profiles has also been dated by the radiocarbon method. A comprehensive reference material of recent pollen from Greenland has been examined. Caryophyllaceae was especially the subject of examination, and a key to the determination of their pollen is presented. The recent pollen sedimentation in the area is elucidated by analysis of the content of pollen in a number of moss cushions. The succession of the plant communities which caused the peat formation is described. The most important feature is the twice occurring change from a dwarf shrub heath to a Sphagnum bog. The radiocarbon datings of these events show close agreement with the re-growth of the European raised bogs at about 700-500 B.C. and A.D. 400 resp. (RY III and RY II).